Top‐down control of carbon sequestration: grazing affects microbial structure and function in salt marsh soils. Issue 5 (17th May 2017) - Mueller, Peter; Granse, Dirk; Nolte, Stefanie; Do, Hai Thi; Weingartner, Magdalena; Hoth, Stefan; Jensen, Kai
Abstract: Tidal wetlands have been increasingly recognized as long‐term carbon sinks in recent years. Work on carbon sequestration and decomposition processes in tidal wetlands focused so far mainly on effects of global‐change factors such as sea‐level rise and increasing temperatures. However, little is known about effects of land use, such as livestock grazing, on organic matter decomposition and ultimately carbon sequestration. The present work aims at understanding the mechanisms by which large herbivores can affect organic matter decomposition in tidal wetlands. This was achieved by studying both direct animal–microbe interactions and indirect animal–plant–microbe interactions in grazed and ungrazed areas of two long‐term experimental field sites at the German North Sea coast. We assessed bacterial and fungal gene abundance using quantitative PCR, as well as the activity of microbial exo‐enzymes by conducting fluorometric assays. We demonstrate that grazing can have a profound impact on the microbial community structure of tidal wetland soils, by consistently increasing the fungi‐to‐bacteria ratio by 38–42%, and therefore potentially exerts important control over carbon turnover and sequestration. The observed shift in the microbial community was primarily driven by organic matter source, with higher contributions of recalcitrant autochthonous (terrestrial) vs. easily degradable allochthonous (marine) sources in grazed areas favoring relative fungal abundance. We propose a novel and indirect form of animal–plant–microbe interaction: top‐down control of aboveground vegetation structure determines the capacity of allochthonous organic matter trapping during flooding and thus the structure of the microbial community. Furthermore, our data provide the first evidence that grazing slows down microbial exo‐enzyme activity and thus decomposition through changes in soil redox chemistry. Activities of enzymes involved in C cycling were reduced by 28–40%, while activities of enzymes involved in N cycling were not consistently affected by grazing. It remains unclear if this is a trampling‐driven direct grazing effect, as hypothesized in earlier studies, or if the effect on redox chemistry is plant mediated and thus indirect. This study improves our process‐level understanding of how grazing can affect the microbial ecology and biogeochemistry of semi‐terrestrial ecosystems that may help explain and predict differences in C turnover and sequestration rates between grazed and ungrazed systems.